Twitter As A Mirror: Examining Public Sentiments Towards Frugal Living From An Islamic Ethical Perspective - Hakim, Lukmanul; Syakiroh, Rofida (Sosial Budaya, 2024)
Nowadays, human needs are increasingly complex. This condition is one of the reasons why people are required to be wise in spending their assets. Frugality is a lifestyle that can be a solution to ensure future economic benefits. This frugal lifestyle is known by urban communities as frugal living. This lifestyle has become a trending topic on social media twitter because it reaps the pros and cons of one's social life. Against this phenomenon, researchers will analyze the sentiment of Indonesian society towards frugal living and study it using the perspective of Islamic law. This research is a qualitative research with a descriptive approach using statistical data of twitter users who write tweets related to frugal living in Indonesia. Twitter users' tweets can be in the form of sentences, photos and videos. In this study, the data used by researchers is only tweets in the form of sentences. This study uses sentiment analysis to determine the sentiment of Twitter users related to frugal living. The tweet data related to frugal living was obtained as many as 4753 with restrictions on Indonesian language from June 1, 2023 to October 23, 2023. Based on the research results, it was found that the most dominant sentiment was neutral with a percentage of 56% or a total of 2655 tweets. The positive sentiment is in second place at 27% or 1296 tweets and the negative sentiment is 17% or 802 tweets. Although the positive sentiment is not dominant, frugal living has a good impact on the life of a Muslim. This lifestyle is in line with religious advice to live simply and moderately in order to prosper and be free from extravagance